Pengaruh Motivasi dan Faktor Lainnya terhadap Kinerja Karyawan Kantor Pusat PT X - Wahyuningtyas, Nadhira; Ananda, Denta Felli (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study objectives is to find out is there any effect from motivation, job satisfaction and human resource development on to employee performance of head office workforce at PT X in Jakarta. Decreasing number of sugar production at 2020 compare to 2021 is a significant phenomenon background of why this research need to be executed. The population in this study are 56 employees of PT X’s head office. Using a non-probability sampling technique, which called saturated sampling method, the data is gathered by questionnaire with Likert Scale. The analytical method used is multiple linear regression. Before testing the hypothesis, the data were analyzed by testing the validity and reliability of research instruments, classical assumptions testing and model’s fit testing using a statistical software programs. Based on the results of hypothesis testing, it shows that motivation does not effect employee’s performance, job satisfaction does not effect employee’s performance, and human resource development effects employee performance of PT X.